2012
DOI: 10.1016/j.electacta.2012.01.097
|View full text |Cite
|
Sign up to set email alerts
|

New inorganic ionic liquids possessing low melting temperatures and wide electrochemical windows: Ternary mixtures of alkali bis(fluorosulfonyl)amides

Abstract: Four kinds of ternary phase diagrams of alkali bis(fluorosulfonyl)amides, LiFSA-NaFSA-KFSA, LiFSA-NaFSA-CsFSA, LiFSA-KFSA-CsFSA and NaFSA-KFSA-CsFSA, have been constructed. All the ternary systems possess the only one eutectic point around equimolar composition with the temperature of 309-318 K. The electrochemical window of the eutectic LiFSA-KFSA-CsFSA ((x Li ,x K ,x Cs)=(0.30,0.35,0.35)) is as wide as 5.4 V at 323 K with the cathode limit being lithium metal deposition. The electrochemical window of the eut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 14 publications
1
36
0
Order By: Relevance
“…The potential of such electrolytes is their superior stability, such as greater thermal stability, large potential window, low vapor pressure, and high boiling points . Whereas organic solvents, such as EC:PC, or EC:DEC, are quite volatile at room temperature, and prone to degradation in a battery, ILs are not.…”
Section: Electrolytes For Nibsmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of such electrolytes is their superior stability, such as greater thermal stability, large potential window, low vapor pressure, and high boiling points . Whereas organic solvents, such as EC:PC, or EC:DEC, are quite volatile at room temperature, and prone to degradation in a battery, ILs are not.…”
Section: Electrolytes For Nibsmentioning
confidence: 99%
“…The potential of such electrolytes is their superior stability, such as greater thermal stability, large potential window, low vapor pressure, and high boiling points. [35][36][37][38] Whereas organic solvents, such as EC:PC, or EC:DEC, are quite volatile at room temperature, and prone to degradation in a battery, ILs are not. This is especially true regarding the anode, as the SEI layer typically forms at the low operational potentials of the anode, leading to inefficiencies, and affecting capacity retention over the long-term cycling.…”
Section: Ionic Liquid Electrolytesmentioning
confidence: 99%
“…(ii) nonflammability, which provides the battery with a level of safety that is important for large-scale application; and (iii) nonvolatility, which prevents the electrolyte from drying or generating pressure at elevated temperatures. We have investigated a series of ILs based on bis(fluorosulfonyl)amide (FSA) anions and bis(trifluoromethylsulfonyl)amide (TFSA) anions, proposed for battery applications at 340-440 K [27][28][29][30]. For instance, the NaFSA-KFSA system is suitable for battery operation around 363 K [31][32][33]; while the NaTFSA-CsTFSA system can be employed at 423 K [34].…”
Section: Introductionmentioning
confidence: 99%
“…The film inhibits the continuous consumption of lithium and plays an important role in the protection of electrode [4,5]. Some studies have shown that, for the electrochemical performance of battery, it is critical to understand whether a layer of film with uniform, stable, low impedance and excellent adhesion properties can be formed [6][7][8]. More importantly, the layer consumes lithium irreversibly on the initial charge of a Li-ion cell, which robs the capacity from the cathode, unless the SEI layer is preformed before the cell assembly [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that, for the electrochemical performance of battery, it is critical to understand whether a layer of film with uniform, stable, low impedance and excellent adhesion properties can be formed [6][7][8]. More importantly, the layer consumes lithium irreversibly on the initial charge of a Li-ion cell, which robs the capacity from the cathode, unless the SEI layer is preformed before the cell assembly [7][8][9]. Therefore, it is of great academic and practical significance to develop the film-forming additives so that the main ingredients of the electrolyte solvent are preferentially decomposed into the uniform and stable SEI film on the graphite negative electrode materials.…”
Section: Introductionmentioning
confidence: 99%